Answer:
![c(1+2+4+5) =1](https://img.qammunity.org/2021/formulas/mathematics/college/urushq6lmfz2fhkvs99m4jtbeeg0wxs30i.png)
![c =(1)/(12)](https://img.qammunity.org/2021/formulas/mathematics/college/kwlcb18x5mw137yxuwwmeahlk0xrgyxls1.png)
Now we can find the expected value with this formula:
![E(Y) =\sum_(i=1)^n Y_i P(Y_i) =\sum_(i=1)^n cy_i *y_i = cy^2_i](https://img.qammunity.org/2021/formulas/mathematics/college/6g8r9spoiei52kycdwcyhzpjor24bzkfqz.png)
And replacing we got:
![E(Y) = (1)/(12) (1^2 + 2^2 + 4^2 +5^2) = (46)/(12)= (23)/(6)](https://img.qammunity.org/2021/formulas/mathematics/college/mrpwt8e86jidfx316d9melz159fsyebq6r.png)
Explanation:
For this case we know the following probability mass function given:
![P(y) = cy , y= 1,2,4,5](https://img.qammunity.org/2021/formulas/mathematics/college/qwxplfekhw3txizhp9qhlzjf1d5eai4cp5.png)
For this case we need to satisfy the following condition in order to have a probability distribution function:
![\sum_(i=1)^n P(y_i) =1](https://img.qammunity.org/2021/formulas/mathematics/college/3b1j1prus80xu3108v3md4ca5vg4lxzmxo.png)
And we have this:
![c(1+2+4+5) =1](https://img.qammunity.org/2021/formulas/mathematics/college/urushq6lmfz2fhkvs99m4jtbeeg0wxs30i.png)
![c =(1)/(12)](https://img.qammunity.org/2021/formulas/mathematics/college/kwlcb18x5mw137yxuwwmeahlk0xrgyxls1.png)
Now we can find the expected value with this formula:
![E(Y) =\sum_(i=1)^n Y_i P(Y_i) =\sum_(i=1)^n cy_i *y_i = cy^2_i](https://img.qammunity.org/2021/formulas/mathematics/college/6g8r9spoiei52kycdwcyhzpjor24bzkfqz.png)
And replacing we got:
![E(Y) = (1)/(12) (1^2 + 2^2 + 4^2 +5^2) = (46)/(12)= (23)/(6)](https://img.qammunity.org/2021/formulas/mathematics/college/mrpwt8e86jidfx316d9melz159fsyebq6r.png)